2012
DOI: 10.3354/esr00459
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparison of single nucleotide polymorphisms and microsatellites for population and demographic analyses of bowhead whales

Abstract: Interest in bowhead whale stock structure has been high due to the species' extreme historical depletion, differential rates of recovery, the potential effects of climate change, and the need to set appropriate quotas for aboriginal hunts. We present an analysis of 42 linked and unlinked single nucleotide polymorphisms (SNPs) among 3 bowhead whale stocks and within the Bering/Chukchi/Beaufort Seas (BCB) stock, and compare results with previously published results of mtDNA control region sequences and 22 micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 77 publications
5
34
0
Order By: Relevance
“…SNPs often prove to be equivalent or better than microsatellites for population genetic and phylogenetic analyses, especially when larger numbers of SNPs can be genotyped (Morin et al . , ; Willing et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…SNPs often prove to be equivalent or better than microsatellites for population genetic and phylogenetic analyses, especially when larger numbers of SNPs can be genotyped (Morin et al . , ; Willing et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The relationships between MS‐ and SNP‐based estimates of N b differed from the N e estimates of bowhead whales ( Balaena mysticetus L.), which did not show a consequent relationship between MS‐ and SNP‐based estimates, including 42 SNPs (Morin et al . ). This could be due to the number of SNPs, as N b based on one SNP per BTLG group (40 SNPs) in the present study also gave a divergent high N b estimate for the W/1+ group.…”
Section: Discussionmentioning
confidence: 97%
“…; Morin et al . ; Weinman et al . ), and the heterozygote excess in all samples is expected in small populations (Robertson ; Rasmussen ), as the background of the HeE method for N b estimation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Morin et al . () found that nearly six times as many SNP loci than microsatellite loci were needed in order to accurately assign samples from two geographically disjunct populations of bowhead whales. Assignment tests can also be applied to AFLP data.…”
Section: Analytical Methods For Evaluating Taxonomic Hypothesesmentioning
confidence: 99%